Full slenderness range DSM approach for stainless steel hollow cross-sections. (June 2017) - Arrayago, I.; Rasmussen, K.J.R.; Real, E.
Abstract: This paper studies the cross-sectional behaviour of austenitic, ferritic and duplex stainless steel hollow sections subjected to several loading conditions and presents a full slenderness range DSM approach for the prediction of cross-sectional strengths. Pure compression, pure bending moment and combined uniaxial bending and compression loading resistances are predicted using the same strength curve, which is based on experimental data gathered from the literature and ultimate strengths generated through parametric studies. The proposed approach is applicable to slender and stocky cross-sections leading to an accurate full slenderness range DSM design approach since the resistance reduction due to local buckling and the effect of strain hardening are taken into account, as is the effect of partial yielding of the cross-section in bending. A new method based on the actual stress distribution of the cross-section is also presented for combined loading conditions, where the cross-sectional behaviour is directly tackled through the same strength curve, providing more accurate results than the methods considering the uncoupled problem. Finally, a statistical analysis is presented to demonstrate the reliability of the proposed DSM approach. Highlights: A full slenderness DSM approach is proposed for stainless steel cross-sections. The approach considers strain hardening and local buckling effects in different loading conditions. A new method is proposed for combined loading considering the actual stress distribution. The new approach provides more accurate results than traditional design methods. The reliability of the approach is statistically demonstrated.